Association between gut microbiota and diabetic nephropathy: a mendelian randomization study - Jin, Yongxiu; Han, Chenxi; Yang, Dongliang; Gao, Shanlin (Frontiers in Microbiology, 2024)
Background The correlation between diabetic nephropathy (DN) and gut microbiota (GM) has been suggested in numerous animal experiments and cross-sectional studies. However, a causal association between GM and DN has not been ascertained. Methods This research adopted MR analysis to evaluate the causal link between GM and DN derived from data acquired through publicly available genome-wide association studies (GWAS). The study utilized the inverse variance weighted (IVW) approach to assess causal association between GM and DN. Four additional methods including MR-Egger, weighted median, weighted mode, and simple mode were employed to ensure comprehensive analysis and robust results. The Cochran’s Q test and the MR-Egger method were conducted to identify heterogeneity and horizontal pleiotropy, respectively. The leave-one-out approach was utilized to evaluate the stability of MR results. Finally, a reverse MR was performed to identify the reverse causal association between GM and DN. Results According to IVW analysis, Class Verrucomicrobiae (p = 0.003), Order Verrucomicrobiales (p = 0.003), Family Verrucomicrobiaceae (p = 0.003), Genus Akkermansia (p = 0.003), Genus Catenibacterium (p = 0.031), Genus Coprococcus 1 (p = 0.022), Genus Eubacterium hallii group (p = 0.018), and Genus Marvinbryantia (p = 0.023) were associated with a higher risk of DN. On the contrary, Class Actinobacteria (p = 0.037), Group Eubacterium ventriosum group (p = 0.030), Group Ruminococcus gauvreauii group (p = 0.048), Order Lactobacillales (p = 0.045), Phylum Proteobacteria (p = 0.017) were associated with a lower risk of DN. The sensitivity analysis did not identify any substantial pleiotropy or heterogeneity in the outcomes. We found causal effects of DN on 11 GM species in the reverse MR analysis. Notably, Phylum Proteobacteria and DN are mutually causalities. Conclusion This study identified the causal association between GM and DN with MR analysis, which may enhance the understanding of the intestinal-renal axis and provide novel potential targets for early non-invasive diagnosis and treatment of DN.